La autonomía universitaria en diálogo A cien años de la Reforma de Córdoba - González Alvarado, Francisco (Editorial Universidad Nacional (EUNA), 2020)
Latin American public institutions of higher education, particularly those in Costa Rica, face important challenges: the enormous task of looking at themselves with a greater critical sense to propose and enable organizational and functional changes that ensure a greater social impact in their substantive work, the imperious need to have secure mechanisms that make possible its financial sustainability in the long term, within the framework of instituting more transparent, systematic and participatory processes of accountability and, finally, the political-social consideration universities, as a social-public asset and a human right, whose primary responsibility falls on the State.